Design and fabrication of laminated veneer lumber classroom chair - Nik Abdullah, Nik Aizan (2010)
There were 2,916,841 secondary students registered in Malaysia for 2000/2001 session,with an estimated increase of about two percent annually. The most essential item required by any school is furniture especially chairs and desks as the number of students increase each year. The increase in demand is also due to frequent damage caused by various reasons. The Ministry of Education spent 33 million ringgit for school furniture in 2008. Given the urgency of the above problem, this research has been undertaken to develop a new classroom chair which is more durable than the current chairs. The study emphasizes on design, material and jointing system used in developing process of the classroom chair. From the interviews and physical observation, it was demonstrated that the current classroom chair is fragile, vulnerable to various types of defect, short life cycle and not repairable. The above problems occurred due to failure in design, as well as the material and jointing used in this current classroom chair. Therefore a new design of classroom chair made of LVL has been developed to overcome the above problems. LVL has been chosen as material for the new design classroom chair as it can be curved to desired shape through a moulding process, allows manufacturing of the chair frame using a single bent blank, hence the new chair design has fewer components to be assembled. According to DƒA principles, less components of the chair will result in less risk of defect and easy to assemble. Bolt and nut are used as jointing systems. The design of the chair also has reduced the risk of defect by aborting the front joint of the chair. According to FRIM standard test, this joint is the most vulnerable part of the current classroom chair. In this study, the current and proposed classroom chair have undergone the FRIM test for strength and stability, the both chairs failed the drop test. However, the damage occurred to the current classroom chair are more critical compared to the proposed LVL classroom chair. The damages are major crack and gapping of the joint between the seat and rear leg. On the other hand, the proposed LVL classroom chair had only a minor crack. In conclusion, this study has proposed a school chair which can be used to replace the current school chair for secondary schools. The proposed LVL classroom chair is not only high in strength and durability, but also has aesthetic and economic values. The findings of this study are useful for further research of LVL classroom chair and also for other LVL products.